2015
DOI: 10.1186/s13012-015-0210-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a tailored implementation programme to improve recognition, diagnosis and treatment of anxiety and depression in general practice: a cluster randomised controlled trial

Abstract: BackgroundAnxiety and depression are not always diagnosed and treated in primary care as has been recommended. A tailored implementation programme, which addresses key barriers for change by targeted interventions, may help to remedy this.MethodsThe effectiveness of an individually tailored implementation programme, additional to standardised training and feedback on the recognition and treatment of patients with anxiety or depression in general practice, was examined in a cluster randomised controlled trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 45 publications
2
46
0
Order By: Relevance
“…From these, (4) the combination of educational meeting and audit/feedback was the most frequent with four studies. 27 42,45 (6) Eight studies used a multifaceted approach, combining more than two methods: distribution of materials, outreach visit and reminders 59 ; educational meetings, outreach visit and audit 28,36 ; outreach visit, audit and practice facilitation 35 ; educational meetings, audit and reminders 38 ; educational meetings, dissemination and networking 30 ; educational meetings, motivational interview and networking 51 ; educational meetings, reminders, audit and feedback, opinion leaders, financial reimbursement, patient-medicated interventions and distribution of educational material. 39 Three studies reported explicitly relying on a theory with regard to the tested intervention: the Theoretical Domains Framework and the Theory of Planned Behaviour, 34 the knowledge translation framework by the Canadian Institutes of Health Research 41 and the RE-AIM framework.…”
Section: Methods Of Interventionmentioning
confidence: 99%
“…From these, (4) the combination of educational meeting and audit/feedback was the most frequent with four studies. 27 42,45 (6) Eight studies used a multifaceted approach, combining more than two methods: distribution of materials, outreach visit and reminders 59 ; educational meetings, outreach visit and audit 28,36 ; outreach visit, audit and practice facilitation 35 ; educational meetings, audit and reminders 38 ; educational meetings, dissemination and networking 30 ; educational meetings, motivational interview and networking 51 ; educational meetings, reminders, audit and feedback, opinion leaders, financial reimbursement, patient-medicated interventions and distribution of educational material. 39 Three studies reported explicitly relying on a theory with regard to the tested intervention: the Theoretical Domains Framework and the Theory of Planned Behaviour, 34 the knowledge translation framework by the Canadian Institutes of Health Research 41 and the RE-AIM framework.…”
Section: Methods Of Interventionmentioning
confidence: 99%
“…Adult oncology clinical trial studies have also described multiple challenges on integrating PRO data in daily care because of the complexity of the disease (eg, high attrition rates during treatment) . It is therefore important to assess which factors might influence the implementation process so that tailored implementation strategies can be developed …”
Section: Introductionmentioning
confidence: 99%
“…30,31 It is therefore important to assess which factors might influence the implementation process so that tailored implementation strategies can be developed. 29,32,33 The aim of the current study was (1) to determine the fidelity of the KLIK method during outpatient consultations shortly after childhood cancer diagnosis in terms of website registration, completion of HRQoL questionnaires, and discussion of KLIK ePROfiles, and (2) to study HCP-reported barriers and facilitators for implementation. First, all HCPs followed the KLIK training 34,35 and received their unique username and password.…”
mentioning
confidence: 99%
“…Examples of the above scenarios are mental health conditions, such as anxiety and depression, stigmatized neurological conditions such as dementia, and chronic conditions which may have a "silent" onset, such as diabetes (18,19). Figures from a range of studies and two meta-analyses shown in Table 1, they show that estimated rates of under-diagnosis for dementia, depression and anxiety, average about 50% (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Further assessments of completeness of EHR data, such as the review by Chan et al (36), show that missingness of parameters such as blood pressure and smoking status can be as high as 38-51%, but are less likely to be missing in populations where these parameters are important for clinical care, such as a high risk cardiovascular disease cohort.…”
Section: Dimensions Of Health Information Quality In Electronic Healtmentioning
confidence: 99%